Diagnostic Performance of High Sensitivity Compared with Contemporary Cardiac Troponin I for the Diagnosis of Acute Myocardial Infarction. (1st October 2017) - Sandoval, Yader; Smith, Stephen W; Thordsen, Sarah E; Bruen, Charles A; Carlson, Michelle D; Dodd, Kenneth W; Driver, Brian E; Jacoby, Katherine; Johnson, Benjamin K; Love, Sara A; Moore, Johanna C; Sexter, Anne; et al.
Abstract: BACKGROUND: We examined the diagnostic performance of high-sensitivity cardiac troponin I (hs-cTnI) vs contemporary cTnI with use of the 99th percentile alone and with a normal electrocardiogram (ECG) to rule out acute myocardial infarction (MI) and serial changes (deltas) to rule in MI. METHODS: We included consecutive patients presenting to a US emergency department with serial cTnI onclinical indication. Diagnostic performance for acute MI, including MI subtypes, and 30-day outcomes were examined. RESULTS: Among 1631 patients, MI was diagnosed in 12.9% using the contemporary cTnI assay and in 10.4% using the hs-cTnI assay. For ruling out MI, contemporary cTnI ≤99th percentile at 0, 3, and 6 h and a normal ECG had a negative predictive value (NPV) of 99.5% (95% CI, 98.6–100) and a sensitivity of 99.1% (95% CI, 97.4–100) for diagnostic and safety outcomes. Serial hs-cTnI measurements ≤99th percentile at 0 and 3 h and a normal ECG had an NPV and sensitivity of 100% (95% CI, 100–100) for diagnostic and safety outcomes. For ruling in MI, contemporary cTnI measurements had specificities of 84.4% (95% CI, 82.5–86.3) at presentation and 78.7% (95% CI, 75.4–82.0) with serial testing at 0, 3, and 6 h, improving to 89.2% (95% CI, 87.1–91.3) by using serial cTnI changes (delta, 0 and 6 h) >150%. hs-cTnI had specificities of 86.9% (95% CI, 85.1–88.6) at presentation and 85.7% (95% CI, 83.5–87.9) with serial testing at 0 and 3 h, improving to 89.3% (95% CI, 87.3–91.2) using a delta hs-cTnI (0 and 3 h) >5 ng/L. CONCLUSIONS: hs-cTnI and contemporary cTnI assays are excellent in ruling out MI following recommendations predicated on serial testing and the 99th percentile with a normal ECG. For ruling in MI, deltas improve the specificity. ClinicalTrials.gov Identifier: NCT02060760